EXPLORATORY FACTOR ANALYSIS FOR THE VALIDITY OF MATHEMATICS LEARNING INDEPENDENCE INSTRUMENTS FOR ELEMENTARY SCHOOL STUDENTS - Ahmad Ahmad; Mariano Dos Santos; Helmiyatun Helmiyatun (El Midad, 2025)
This study aims to test the validity of the mathematics learning independence instrument of elementary school students using Exploratory Factor Analysis (EFA). The research method used is a quantitative approach with factor analysis techniques to identify the latent structure of the instrument. Data was collected through a questionnaire of 73 grade V elementary school students and analyzed using Kaiser-Meyer-Olkin (KMO), Bartlett's Test, and factor extraction with Principal Component Analysis (PCA). The results of the study show that this instrument consists of five main factors that have a significant correlation with the aspect of mathematics learning independence. The model match index shows good values, with RMSEA = 0.00 and TLI = 1.1705, signifying that this instrument is valid and reliable. However, some items with a loading factor below 0.40 and a high uniqueness (u²) value were found, indicating that the items did not fully represent the measured factor. Therefore, it is necessary to revise or eliminate items that have high cross-loading as well as add more specific items according to the dimension of mathematics learning independence. Thus, the developed instruments can be used in research and educational practice to measure the independence of elementary school students' mathematics learning, while still paying attention to the improvement of the instrument in advanced studies.